An analysis of surface integrity when drilling inconel 718 using palm oil and synthetic ester under, MQL condition - A. Rahim, Erween; Sasahara, Hiroyuki (Taylor & Francis, 2011)
The components being manufactured in the aerospace industry must be capable of being utilized for long periods without failure. Thus, the functional behavior of these machined components is greatly dependent upon their surface integrity. The present work compares the performance of palm oil and synthetic ester on surface integrity during drilling of Inconel 718. The results indicate the substantial benefit of the minimum quantity of lubrication (MQL) by palm oil on microhardness, surface roughness, surface defects and sub-surface deformation.